Análise do isomorfismo na constituição do arranjo organizacional "Coordenação de Curso de Graduação" em quatro centros universitários do interior do Estado de São Paulo - Gonzalez, Fernanda Nolli (Universidade Federal de São Carlos, 2009)
This work analyses the organizational arrangement isomorphism of graduation course coordination of the university center institutional model. This model has been regulated in the higher education since 1996 with the new Law of Guidelines and Basis of Education (Lei de Diretrizes e Bases da Educação). Taking into account that the educational institutions submit to the authoritative force of the legislation determined by the Educational Ministry, the course was taken as a referential to describe the structure framing facing the legal demands. This is the main focus of preoccupation of the university center because it is through this framing that teaching is transmitted. To achieve the target of this work a bibliographical research has been carried out on the institutional theory, on the new institutionalism and on bureaucracy characteristics and types of organizational structures. In addition to it, a case study has also been carried out with the courses of Administration and Social Communication Publicity and Advertisement in four university centers (three private institutions and one public institution) in the country of São Paulo State. One chairperson of each institution was interviewed, as well as the coordinators of the courses above mentioned, in a total of twelve researches. The isomorphism of the organizational arrangement in the graduation course coordination has been identified specially on the issues pre-established by law. Comparing the same courses, it has been observed that the courses of Administration are more isomorphic than the courses of Social Communication Publicity and Advertisement. Besides, a flexibility trend of the organizational structure of the institutions has been verified and this is meant to conform to the environmental uncertainties, that is to say, the existence of a mechanical structure (inheritance of the departmental framing) together with an organic structure. This factor also reflects on the difference between the form of course management where coordinators under the same internal regimen orientation print on the course their identity and their way of managing.
Keywords: Teoria da organização; Estrutura organizacional; Ensino superior; Isomorfismo; Centro universitário; Organizational structure; Isomorphism; University center; ENGENHARIAS::ENGENHARIA DE PRODUCAO